2018
DOI: 10.1111/ap.12251
|View full text |Cite
|
Sign up to set email alerts
|

Resilience and Subjective Wellbeing: A Psychometric Evaluation in Young Australian Adults

Abstract: Objective: Resilience is an important and underdeveloped area of research, and there are few studies that describe levels of resilience among youth samples. A major aim of this research is to explore the utility of an adapted form of the 10-item Connor Davidson Resilience Scale and to clarify the association between this construct and a robust measure of subjective wellbeing. Method: A representative sample of 1000 Victorians aged 16-25 years participated in a telephone interview comprising the modified 10item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
31
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 29 publications
1
31
0
6
Order By: Relevance
“…In addition, resilience showed significant correlation with positive mental health indicators, such as life satisfaction and subjective well-being (Haddadi and Besharat, 2010;Vitale, 2015;Satici, 2016;Tomyn and Weinberg, 2016). Tomyn and Weinberg (2016) found a moderate, positive correlation between resilience and subject well-being. Satici (2016) showed that resilience positively predicts subjective well-being through the mediating role of hope.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…In addition, resilience showed significant correlation with positive mental health indicators, such as life satisfaction and subjective well-being (Haddadi and Besharat, 2010;Vitale, 2015;Satici, 2016;Tomyn and Weinberg, 2016). Tomyn and Weinberg (2016) found a moderate, positive correlation between resilience and subject well-being. Satici (2016) showed that resilience positively predicts subjective well-being through the mediating role of hope.…”
Section: Introductionmentioning
confidence: 96%
“…The studies addressing the relationship between resilience and mental health are mostly cross-sectional studies, while data analysis methods are centered on correlation and regression analysis (Abolghasemi and Varaniyab, 2010;Anderson, 2012;Skrove et al, 2012;Goldstein et al, 2013;Vitale, 2015;Tomyn and Weinberg, 2016), with some studies using the intermediate effect or regulatory effect analysis (Liu et al, 2012;Satici, 2016;Ding et al, 2017;Poole et al, 2017;Shapero et al, 2019). However, follow-up studies are generally insufficient: the temporal effects relationship between resilience and mental health could not be determined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A common concern regarding resilience is that it can only be demonstrated in the face of adversity and therefore the a priori examination of resilience is a rather difficult task [11]. Resilience metrics usually assessing actual resilience by approaching "perceived resilience".…”
Section: Introductionmentioning
confidence: 99%
“…Resilience metrics usually assessing actual resilience by approaching "perceived resilience". In this sense, survey respondents subjectively rate their level of agreement with specific statements expressing resilience properties [11].…”
Section: Introductionmentioning
confidence: 99%